Democratic Tipping Points - Antonio Ciccone (Center for Economic Studies and ifo Institute (CESifo), 2018)
I examine whether transitory events can tip the scales against authoritarian regimes and lead to persistent democratization. I think of situations where this is a possibility as democratic tipping points. The transitory events I focus on are rainfall shocks in the most agricultural countries in the world. I show that while these shocks only affect agricultural output contemporaneously, they have persistent effects on political institutions. Authoritarian regimes experiencing negative rainfall shocks are more likely to be democratic three, five, and ten years later.
Keywords: 330; transitory shocks; persistent democratization